Development of human machine interface oriented to processes control. - Ruíz Lizama, Edgar (2008)
The problem that is approached in the present article is the following one: How to elaborate a communication fast and easy to understand and, simultaneously, oriented to the process control with a automated mixer? During the research development it will appreciate the main criterias to consider for its design, as well as the type of programming will be used. As result obtained a software SCADA whose Human Machine Interface (HMI) will be the contact of man with the process to control.